Avian influenza: global assessment of potential pandemic of the twenty first century - Abubakar, Mustapha Bala; Ideris, Aini; Omar, Abdul Rahman; Bejo, Mohd Hair (WFL Publisher, 2009)
The emergence of highly pathogenic avian influenza (HPAI) of Asian lineage and the subsequent spillover to other parts of the globe and spread of Eurasian-Africa H5N1 epidemic into domestic, wild birds and human have generated unprecedented attention in recent times and threat of potential pandemic via the avian-human link. Historically, from 1878 through 1955, fowl plaque was described as a high mortality disease of poultry in many countries throughout Europe, Asia, North and South America and Africa and the etiology was proved to be a filterable virus. In the 1930s through the 1950s, fowl plaque disappeared as an endemic disease in most part of the world. In 1949, the first report of a low virulent disease in chickens caused by LPAI virus was reported. In 1955, the etiology of fowl plaque was determined to be influenza A virus, which subsequently was identified as the H7 subtype. In 1959, a “fowl plaque-like” outbreak was described in chickens, which was the first report of fowl plaque caused by a non-H7 AI virus, i.e. first fowl plaque outbreak from H5 subtype of AI virus. In 1961 the first wild birds infection and deaths were reported in common terns of South Africa. In 1966 and 1971, the first H5 and H7 LPAI viruses, respectively, were identified; prior to this period, only HPAI viruses had H5 and H7 subtypes. In 1970, the AGID serological test was introduced, which allowed easy and rapid identification of AI virus-infected poultry flocks. In 1972, there was the first isolation of LPAI viruses in asymptomatic wild birds: ducks in the United States and shorebirds in Australia. In 1981, the term “highly pathogenic avian influenza” was accepted as standard nomenclature for fowl plaque and related synonyms. In 1983, LPAI virus was observed mutating to HPAI virus during LPAI field outbreak, and specific genomic changes were identified in the proteolytic cleavage site of the hemagglutinin responsible for the virulence change. In the late 1980s and early 1990s, molecular criteria were added to the definition for classifying an AI virus as HPAI. In 2002, there were the first reported infections and deaths in a wide variety of wild bird species from AI virus H5N1 HPAI virus. The primary goal of this review is to highlight the global situation of HPAI and provide baseline information to show the potential pandemic nature of the virus, so that control and prevention strategies can be improved.